Lifelong Religion as Habitus Religious Practice among Displaced Karelian Orthodox Women in Finland - Kupari, Helena (Numen Book Series, 2016)
In this book, Helena Kupari examines the lived religion of elderly Finnish Orthodox Christian women, displaced from Karelia in the aftermath of the Second World War, through an innovative reading and application of Pierre Bourdieu's practice theory. Readership: Scholars and students interested in women's religion, minority religion, religion and migration, Orthodox Christianity in Finland, and Pierre Bourdieu's social theory as applied to lived religion.